THE MENTAL HEALTH OF A TEACHER: LUXURY OR NECESSITY - Natalia MACHYNSKA; Mariia OLIINYK (Association of Social and Educational Innovation, 2024)
The article provides a theoretical analysis of the teacher's mental health, offers practical advice on overcoming certain factors of health disorders; attention is focused on the importance of allocating time to perform various tasks. The educational reforms of the domestic society, which bring actual changes in the training and professional formation of future specialists, should be distinguished not only by significant development and educational potential, but also should preserve the health of all participants in the educational process. Nowadays, last task remains unsolved. Due to the high emotional intensity of the educator's professional activity, non-standard pedagogical situations, responsibility and complexity of the teacher's professional work, the risk of developing the syndrome of "emotional burnout and exhaustion" increases. At the same time, very little attention is paid to effective psychological-pedagogical and medical technologies, which are aimed at preserving the teacher health, reducing the risk of the formation of the "emotional burnout" syndrome and the appearance of a crisis in the profession as a whole. The problem of individual living psychological health in an unstable, changing world, complex, extreme socio-ecological conditions, became particularly relevant at the beginning of the XXI century i.e. the century of human science. Increased interest in a person as a subject of work drew the researchers' attention to the changes that occur with a person in the process of performing professional activities.  The problem of preserving and protecting each individual mental health is one of the most urgent issues of professional activity and professional growth of specialists in various fields in current conditions i.e. a full-scale invasion of russia on the territory of Ukraine. Professional activity in modern conditions of uncertainty, constant tension and anxiety is characterized by significant physical and psycho-emotional stress, which determines the existence of significant violations or loss of mental health.